Efektivitas Kinesiotapping dalam Menurunkan Nyeri LBP pada Lansia - Fiqi, Fiqi WIdyawati; Tri Utami; Vira Khoirul Nissa (STIKes Ibnu Sina Ajibarang, 2025)
LBP is a clinical syndrome characterized by the onset of pain symptoms around the lower back that are without or can be accompanied by lower leg radiance. LBP complaint factors usually occur at the age of 35 years, because bone compaction begins to experience degeneration such as tissue damage, decreased fluid levels cause bone and muscle stability to decrease. Muscle strength will decrease when the age is >60 years. The Kinesiotaping method is a physiotherapy modality to correct and improve musculoskeletal disorders with a natural healing process, one of which can relieve LBP pain complaints. LBP pain greatly interferes with daily activities. Method: The research method uses quantitative descriptive. Research design with one group pretest-posttest design. The location of the study was carried out at CFD Colomadu, Karanganyar Regency - Central Java in July 2024. The study population was 40 respondents. Data collection techniques in the form of questionnaire instruments Keele Start Back Screening Tool. Result: Respondent characteristics based on the age of the elderly who participated in CFD in Colomadu and participated in the health examination were aged >60 years totaling 40 people (40.0%), with the most LBP incidents in the minimal disability category totaling 20 people (50.0%). Respondent characteristics based on the gender category in the elderly CFD in Colomadu and participated in the health examination were mostly women totaling 25 people (62.5%), while men totaling 15 people (37.5%). Conclusion: The majority of LBP incidents were minimal disabilities.